Radiofrequency ablation vs. cryoablation for pediatric atrioventricular nodal reentrant tachycardia in the era of three-dimensional electroanatomical mapping - Chan, Yao-Wei; Chuang, Chieh-Mao; Lee, Pi-Chang; Tai, I-Hsin; Peng, Ying-Hsuan; Fan, Wen-Po; Lee, Yu-Shin; Lin, Ming-Chih; Jan, Sheng-Ling; Fu, Yun-Ching; Chen, Shih-Ann (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCryoablation for pediatric atrioventricular nodal reentry tachycardia (AVNRT) is favored for reducing conduction system injury compared to radiofrequency (RF) ablation. The safety advantage of cryoablation over RF ablation primarily results from studies conducted without a three-dimensional electroanatomical mapping (3D EAM) system. Currently, 3D EAM systems offer precise and efficient guidance, improving safety and outcomes. This study compares RF ablation and cryoablation using a 3D EAM system for pediatric AVNRT treatment.MethodsA retrospective study enrolled consecutive pediatric patients with AVNRT who underwent RF ablation (RF group) or cryoablation (Cryo group) guided by a 3D EAM system at multiple centers from July 2018 to January 2024.ResultsAmong 95 patients, 69 received RF ablation and 26 received cryoablation. Recurrence rates were 2.9% in the RF group and 0% in the Cryo group (p > 0.99), with no difference in AVNRT-free survival. No major complications, such as permanent atrioventricular (AV) block, were observed. The minor complication rates, including transient AV block, did not differ significantly (14.5% vs. 11.5%, p > 0.99). The RF group had a significantly shorter procedure time (111 vs. 153.5 min, p = 0.005). Ablation outside the low Koch triangle and cryoablation were independently associated with longer procedure times. The procedure time decreased significantly in the recent 50% of RF ablation cases, but not in cryoablation cases.ConclusionWith 3D EAM guidance, both RF ablation and cryoablation are considered safe and effective for pediatric AVNRT. RF ablation is more efficient with a shorter procedure time after increasing experience.